Positive association between nonalcoholic fatty liver disease and growth hormone deficiency in patients with nonfunctioning pituitary adenoma - Hwang, Yoon-a; Lee, Hye Won; Ahn, Sang Hoon; Lee, Eun Jig; Ku, Cheol Ryong; Kim, Seung Up (Frontiers in Endocrinology, 2023)
Objective: Non-alcoholic fatty liver disease (NAFLD) is characterized by growth hormone deficiency (GHd). We investigated the association between NAFLD and GHd in patients with nonfunctioning pituitary adenomas (NFPA). Design and Methods: We recruited patients with NFPA who underwent transsphenoidal adenectomy between January 2005 and December 2018. Pituitary function was determined by the insulin tolerance test, thyroid hormone assay, and gonadal hormone levels. NAFLD was defined as a hepatic steatosis index greater than 36. Results: Among 278 patients (mean age, 44.2 years; 58.6% [n=163] female), 103 (37.0%) had GHd, 139 (50.0%) had hypogonadism, and 75 (27.0%) had NAFLD. The prevalence of NAFLD was significantly higher in patients with GHd than in those without (36.9% vs. 21.1%, p=0.01). Even after adjusting for age, total cholesterol level, and gonadal function, patients with GHd had a two-fold higher prevalence of NALFD than those without GHd (adjusted odds ratio [OR]=2.03, 95% confidence interval [CI]=1.17–3.55, p=0.01). Among female patients, the prevalence of NALFD was significantly higher in those with GHd than in those without (adjusted OR=2.40, 95% CI=1.04–5.56, p=0.04); whereas, among male patients, the prevalence of NAFLD was statistically similar between those with and without GHd (p>0.05). In addition, gonadal function did not affect the prevalence of NAFLD in patients with NFPA (29.3% with eugonadism vs. 47.8% with hypogonadism, p=0.14). Conclusion: Among patients with NFPA, the prevalence of NAFLD was two-fold higher in patients with GHd than that in those without GHd. Thus, screening for NAFLD might be required in NFPA patients with GHd.